PENGARUH LATIHAN KNEES OVER TOES DAN DEPTH JUMP TERHADAP PENINGKATAN DAYA LEDAK LONCATAN ATLET BOLA BASKET - Ariyanto, Adi; Rudi; Sofyan, Davi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vertical jumping ability is a physical condition component that greatly determines basketball performance, particularly in executing rebound, jump shoot, lay-up shoot, and block techniques. This study aimed to determine the effect of knees over toes and depth jump training on improving the jumping power of basketball athletes at Pamizen Club. A pre-experimental method with a one group pretest-posttest design was employed. The sample consisted of 18 novice athletes selected through purposive sampling. The treatment was administered for 4 weeks (12 sessions) at a frequency of 2-3 times per week. Data were collected using the vertical jump test (Sargent test) and analyzed using a paired sample t-test at a 5% significance level with SPSS 27. The results showed an increase in the mean vertical jump score from 42.61 cm (pretest) to 46.11 cm (posttest), with a t-value of 11.468, df 17, and significance <0.001 (p < 0.05). It can be concluded that knees over toes and depth jump training had a positive and significant effect on improving the jumping power of basketball athletes.